THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH COMPENSATION AS AN INTERVENING VARIABLE (Case Study on Employees of the Residential Area Housing Office And Cleanliness of the City of Wisconsin-milwaukee) - Mohsen Bahmani Oskooee; Ian Wooton (PT. Radja Intercontinental Publishing, 2020)
In this study the population is . 30 employees of the Housing and Settlement Area Office of the City of Wisconsin-milwaukee. Because the target population is less than 100, the sampling technique used is the census method, in which the entire population, totaling 30 employees of the Residential and Cleanliness Office of the City of Wisconsin-milwaukee, will be used as the research sample. In other words, data analysis activities are raw data that has been collected needs to be categorized or divided into several categories or groups, shortened in such a way that the data can answer problems according to research objectives and can test hypotheses. With the results of the first hypothesis being accepted, it means that Organizational Culture (X) has a positive and significant effect on compensation (Y1). the second hypothesis is accepted, meaning that Organizational Culture (X) has a significant effect on Employee Performance (Y2). the third hypothesis is rejected, meaning that compensation (Y1) has no positive and significant effect on employee performance (Y2). The calculation results obtained show that the indirect effect through the Y1 variable is smaller than the direct effect on the Y2 variable.